Effect of ultrafiltration concentration level of milk and inoculum level on interrelationship between titratable acidity development and pH drop during incubation of dahi - Khurana, Sakshi; Gupta, Dr Vijay Kumar (Indian Journal of Dairy Science, 2014)
The simultaneous effects of ultrafiltration concentration level (UFCL) (1(skim milk), 2, 2.2 and 2.5-fold) and inoculum level (0.3% and 0.5%, v/v) on the acidification process in ultrafiltered (UF) cow milk fermented with dahi culture were investigated. The interrelationship between pH and titratable acidity (TA) changes with change in protein content of milk. Highly significant (p<0.01) increase was observed in rate of TA development and of pH drop during incubation of dahi with increase in UFCL of SM from 1-fold UF to 2.5-fold UF. Dahi prepared from different UF concentrated milks did not achieve pH 4.6 even until 12 h of incubation, while acidity was around 0.9%. The rate of TA development was highly significantly (p<0.01) faster in dahi prepared from UF concentrated milk as compared to the conventionally prepared one.